Manajemen Bisnis dalam Pengembangan Minapadi Organik pada P4S Bengkel Mimpi di Desa Kanigoro Kecamatan Pagelaran Kabupaten Malang - Isti'anah, Dewi; Relawati, Rahayu (Universitas Galuh, 2026)
Sustainable agriculture is a solution to soil degradation, climate change, and excessive use of chemicals. The organic minapadi system, which integrates rice and fish cultivation in a single ecosystem, is considered capable of improving land efficiency and farmers' income in an environmentally friendly manner. This study aims to analyze the business management and feasibility of organic minapadi operations at P4S Bengkel Mimpi in Malang Regency, which has been in operation for over a decade. The research was conducted from February to April 2025 using a quantitative descriptive method with purposive sampling techniques. Primary data were obtained through observation, interviews, questionnaires, and documentation. The analysis included production costs, revenue, income, business efficiency (R/C ratio), and long-term investment feasibility (NPV, IRR, Net B/C, and Payback Period). The results showed total costs per growing season of Rp57,016,301, with revenues of Rp76,576,000, resulting in net income of Rp19,559,699. The R/C ratio of 1.3 indicates that the business is viable. A 10-year investment analysis yielded a positive NPV of Rp321,484,569, an IRR >100%, a Net B/C of 1.30, and a payback period of only 0.66 years, indicating very rapid capital turnover. In conclusion, organic minapadi with integrated management between rice cultivation, fish farming, and aquaponics systems can serve as a productive, efficient, and profitable sustainable agriculture model with good development prospects.